Study of Electrocardiographic Changes and Spirometry Findings in Chronic Obstructive Lung Disease - Pandey, Tilchan; Khanal, Jeevan; Gautam, Resham; Pokhrel, Shami (Journal of Nepalgunj Medical College, 2023)
Introduction: Chronic Obstructive Pulmonary Disease is one of the top three causes of death worldwide and patients have to do pulmonary function test by spirometry to diagnose and to evaluate the severity. Electrocardiogram abnormalities have been found uniformly increasing with the severity by Global Initiative for Obstructive Lung Disease stages. Aims: To know the role of Electrocardiogram in the evaluation of severity of Chronic Obstructive Lung Disease. Methods: This was conducted in the department of Internal Medicine of Lumbini Medical College Teaching hospital from December 2021 to June 2022. The Chronic Obstructive Pulmonary Lung Disease was established with history, examination and spirometry along with Electrocardiogram. Results: Among 72 patients included 40 (55.56%) were in mild to moderate stage and 32 (44.44%) were in severe stage. The mean Force Expiratory Volume in one Second/Force Vital Capacity of severe stage was 38.59± 6.9 and 66.32±7.37 in mild to moderate stages. The electrocardiographic abnormalities like right atrial enlargement (P –pulmonale), right ventricular hypertrophy, complete right bundle branch block, low voltage in limbs, right axis deviation, sinus tachycardia and supraventricular tachycardia were seen in severe stage with statistical significance (p<0.05). Whereas left axis deviation and premature atrial contraction were found in mild to moderate disease and was statistically not significant.Increased percentage of normal electrocardiogram was found in mild or moderate than severe stage with statistical significance. So it is inversely related with the severity of disease. Conclusion: The relationship between Electrocardiogram findings and degree of airway obstruction was found to be highly significant. So, Electrocardiogram can be used as a surrogate investigation to evaluate the severity of Chronic Obstructive Pulmonary Disease.